Fluorescent Dye-Doped Brightening Polymer-Stabilized Bistable Cholesteric Liquid Crystal Films - Zhao, Yuzhen; Li, Chaonian; Lang, Tingting; Sun, Yitian; Li, Qingbo; Shi, Xinli; Yao, Ruijuan; Zhang, Huimin; Zhao, Yang (Molecules (Basel, Switzerland), 2023)
Brightening polymer-stabilized bistable cholesteric liquid crystal (PSBCLC) films with doped fluorescent dyes were prepared using the polymerization-induced phase separation (PIPS) method. The transmittance performance behavior of these films in both states (focal conic and planar) and absorbance change in multiple dye concentrations were studied using a UV/VIS/NIR spectrophotometer. The change occurring in dye dispersion morphology with different concentrations was obtained by means of the polarizing optical microscope. The maximum fluorescence intensity of different dye-doped PSBCLC films was measured using a fluorescence spectrophotometer. Moreover, the contrast ratios and driving voltages of these films were calculated and recorded to demonstrate film performance. Finally, the optimal concentration of dye-doped PSBCLC films with a high contrast ratio and a relatively low drive voltage was found. This is expected to have great potential applications in cholesteric liquid crystal reflective displays.